The sublime perversion of capital : Marxist theory and the politics of history in modern Japan - Walker, Gavin, 1979- (Asia-Pacific., 2016)
In The Sublime Perversion of Capital Gavin Walker examines the Japanese debate about capitalism between the 1920s and 1950s, using it as a ""prehistory"" to consider current problems of uneven economic development and contemporary topics in Marxist theory and historiography.